Social Media Marketing Adoption among SMEs in Malaysia and Nigeria (S/O 14089) - Ramanchandram, Rajoo; Abdullah, Shahmir Sivaraj; Kolandaisamy, Indraah; Soo, Hooi Sin; Mohd Jani, Mohamad Yusop (UUM, 2020)
Entrepreneurship is the cornerstone for developing new businesses, products, services, or processes which have an ability to enhance socio-economic development but it will not succeed without the infusion of technology in its operations. The study has found that facilitating conditions have a significant influence on social media marketing adoption by SME’s in Malaysia and Nigeria. Even though the rate of use of social media is high both in Malaysia and Nigeria but there is still much to improve especially in the advent of IR 4.0. This obviously influences perceived ease of use and perceived usefulness on social media marketing adoption among SME’s. The situation is similar in Malaysia and Nigeria as was indicated by the data. As behaviour is influenced by external stimuli the pervasiveness of technology is very much evident in everyday life. This factor coupled with education, family history and primarily the environment encourages adoption. The attributes of technology does have the tendency to influence the same type of behaviour within entrepreneurs. The study has also confirmed that the major component that influences the adoption of technology is its perceived value or its usefulness for the entrepreneur. SME’s on their part are driven by the entrepreneur which had led to the realisation that technology cannot be stopped but what type of technology will enhance their operational effectiveness. It is not surprising that the relevant factors above have a strong bearing in both Malaysia and Nigeria even though they are continents apart. This study is essential to scholars and other researchers; to government policy makers and to investors. In the scholarly field, few studies have been done to determine why entrepreneurial intention has not been emphasized by universities. This will, therefore, provide input for further research or discussions that will find the study relevant in the scholarly field of entrepreneurship. By incorporating and understanding these findings more focussed plans could be implemented to disseminate the relevance of technology in the present business environment. This may include education, supporting policies and social environment which are expected to change and evolve. As these SME’s in Malaysia and Nigeria succeed it will inadvertently enhance the goal of promoting employment in Malaysia and Nigeria. This is even more important now in the COVID 19 era.